Returns and spillover of Colorado agricultural research-computable general equilibrium model for livestock - Fathelrahman, Eihab M., author; Hoag, Dana L., advisor; Davies, Stephen P., advisor; Weiler, Stephen, committee member; Seidl, Andy, committee member (Colorado State University. Libraries, 2002)
Objectives of this dissertation include study of the implication of investment and returns to livestock research in Colorado as case studies for the Northern Plains Region, description of the components of Colorado regional CGE model of livestock production to analyze direct, indirect and induced impact of investment in livestock research and development of investment recommendations regarding implications of estimation of returns to investment in livestock research in Colorado case study to the regional livestock research policy in the Northern Plains. Starting from initial rate of return of 20%, the estimated ROR was found to be 16%, all direct benefits to the beef as well as all agricultural and non-agricultural sectors included the ROR rises to 25%. When indirect benefits are included, the ROR is estimated to be 28%. When induced effects also added to the benefits of research ROR rise to 35%. Then the CGE model used to simulate 40% ROR to (beef and diary). When all direct benefits (targeted and non-targeted) are included ROR rise to 64%. However, when Indirect benefits included the ROR is estimated to be 76%. When induced effects also added to the benefits of research ROR rise to 104%. Starting from initial rate of return of a 60% ROR to all livestock research the estimated ROR found to be 57%. When all direct benefits (targeted and non-targeted) to the livestock sector as well as all agricultural and non-agricultural sectors are included the ROR rise to 73%. When indirect benefits included the ROR is estimated to be 86%. When induced effects also added to the benefits of research ROR rise to 117%. Investment in livestock research affect returns to factors of production and households income significantly. At 40% ROR to livestock R&D there is about 1% increase in returns to factors of production. The basic livestock research clearly contributes to higher returns to factors of production, and higher income to all household categories. The middle-income group witnesses a slightly higher impact than the low and high-income categories.
Keywords: research; livestock; studies; mathematical models; beef; software; feeds; agricultural production; food; investments; prices; research and development -- randd; expenditures; case studies; simulation; experiments; regions; poultry